Fungal Infections Are Not Associated with Increased Mortality in COVID-19 Patients Admitted to Intensive Care Unit (ICU) - Ainsworth, James; Sewell, Peter; Eggert, Sabine; Morris, Keith; Pillai, Suresh (Critical Care Research and Practice, 2023)
Introduction. Fungal infection is a cause of increased morbidity and mortality in intensive care patients. Critically unwell patients are at increased risk of developing invasive fungal infections. COVID-19 patients in the intensive care unit (ICU) may be at a particularly high risk. The primary aim of this study was to establish the incidence of secondary fungal infections in patients admitted to the ICU with COVID-19. Secondary aims were to investigate factors that may contribute to an increased risk of fungal infections and to calculate the mortality between fungal and nonfungal groups. Methods. We undertook a retrospective observational study in a tertiary ICU in Wales, United Kingdom. 174 patients admitted with COVID-19 infection from March 2020 until May 2021 were included. Data were collected through a retrospective review of patient’s clinical notes and microbiology investigation results obtained from the online clinical portal. Results. 81/174 (47%) COVID-19 patients developed fungal infections, 93% of which were Candida species, including Candida albicans (88%), and 6% had an Aspergillus infection. Age and smoking history did not appear to be contributing factors. The nonfungal group had a significantly higher body mass index (33 ± 8 vs. 31 ± 7, p=0.01). The ICU length of stay (23 (1–116) vs. 8 (1–60), p<0.001), hospital length of stay (30 (3–183) vs. 15 (1–174) ± 7, p<0.001), steroid days (10 (1–116) vs. 4 (0–28), p=0.02), and ventilation days (18 (0–120) vs. 2 (0–55), p<0.001) were significantly higher in the fungal group. The mortality rate in both groups was similar (51% vs. 52%). The Kaplan–Meier survival analysis showed that the fungal group survived more than the nonfungal group (log rank (Mantel–Cox), p<0.001). Conclusion. Secondary fungal infections are common in COVID-19 patients admitted to the ICU. Longer treatment with corticosteroids, increased length of hospital and ICU stay, and greater length of mechanical ventilation significantly increase the risk of fungal infections. Fungal infection, however, was not associated with an increase in mortality.